Correlates of neutralizing/SARS-CoV-2-S1-binding antibody response with adverse effects and immune kinetics in BNT162b2-vaccinated individuals - Maeda, Kenji; Amano, Masayuki; Uemura, Yukari; Tsuchiya, Kiyoto; Matsushima, Tomoko; Noda, Kenta; Shimizu, Yosuke; Fujiwara, Asuka; Takamatsu, Yuki; Ichikawa, Yasuko; Nishimura, Hidehiro; Kinoshita, Mari; et al. (Scientific reports, 2021)
While mRNA vaccines against SARS-CoV-2 are exceedingly effective in preventing symptomatic infection, their immune response features remain to be clarified. In the present prospective study, 225 healthy individuals in Japan, who received two BNT162b2 doses, were enrolled. Correlates of BNT162b2-elicited SARS-CoV-2-neutralizing activity (50% neutralization titer: NT 50 ; assessed using infectious virions) with various determinants were examined and the potency of sera against variants of concerns was determined. Significant rise in NT 50 s was seen in sera on day 28 post-1st dose. A moderate inverse correlation was seen between NT 50 s and ages, but no correlation seen between NT 50 s and adverse effects. NT 50 s and SARS-CoV-2-S1-binding-IgG levels on day 28 post-1st dose and pain scores following the 2nd dose were greater in women than in men. The average half-life of NT 50 s was ~ 68 days, and 23.6% (49 out of 208 individuals) failed to show detectable neutralizing activity on day 150. While sera from elite-responders (NT 50 s > 1,500: the top 4% among the participants) potently to moderately blocked all variants of concerns examined, some sera with low NT 50 s failed to block the B.1.351-beta strain. Since BNT162b2-elicited immunity against SARS-CoV-2 is short, an additional vaccine or other protective measures are needed.